Antioxidant enzyme activities in chili plants in response to the infection of Pepper yellow leaf curl Indonesia virus - Paradisa, Yashanti Berlinda; Hidayat, Sri Hendrasturi; Mutaqin, Kikin Hamzah; Syukur , Muhamad; Wahyuni, Wahyuni; Indrayani, Sri; Sulistyowati, Yuli; Fidriyanto, Rusli (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2026)
Chili pepper is an important agricultural crop but is highly vulnerable to viral diseases, including Pepper yellow leaf curl Indonesia virus (PepYLCIV). This study investigated the biochemical response of chili plants to PepYLCIV infection by examining changes in antioxidant enzyme activities: peroxidase (POD), catalase (CAT), and ascorbate peroxidase (APX). The effects of sample handling methods on enzyme activity measurements were also evaluated. The experiment was conducted in a biosafety greenhouse using a factorial design with four replications. The treatments included two chili varieties (Bara and Bonita), plant condition (healthy and PepYLCIV-infected), sample types (fresh leaf tissue and frozen leaf tissue stored at −80 °C), and seven sampling times (1, 3, 5, 7, 14, 21, and 28 days post-inoculation). Result showed that POD activity was significantly higher in infected plants than in healthy plants, whereas CAT and APX activities showed no significant differences between plant health conditions. Fresh samples consistently exhibited higher enzyme activity than frozen samples. POD and CAT activities peaked at 28 days post-inoculation, while APX activity was the highest at 5 days post-inoculation and fluctuated over time. These findings highlight the importance of considering infection status, sampling time, and sample processing when evaluating antioxidant enzymes in plant–virus interaction studies.